Integracja osoby czyli rzecz o "pedagogicznych poglądach" Jiddu Krishnamurtiego = Integration of the person or thing about the "pedagogical views" of Jiddu Krishnamurti - Kopaczyńska, Iwona (Zielona Góra: Uniwersytet Zielonogórski)
The author presents pedagogical aspects of Jiuduu Krishnamurti's views in the contextof integration ideas. She points to the basics of his pedagogical thought concentrated around the three questions: Who teaches? What teaches? How teaches? On the basis of the analysis ofJiuduu Krishnamurti's views, the author makes an attempt to answer the three asked questions. She presents the essential concepts of the thinker's teachings which lead to the integration of a person.
Keywords: pedagogika; Krishnamurti, Jiddu (1895-1986)